Effects of gender and personality on experience of small living spaces: Ceiling height and floor plan shape in virtual environment - Lee, Seo-Young; Yoon, So-Yeon (Frontiers in Virtual Reality, 2022)
Virtual reality (VR) technology has been used as a design research tool to enable a virtual experience of space as a real-life-scale mock-up. In terms of user experience design research, VR is highly scalable and adjustable, meaning that designed virtual prototypes and environments can be tested on a diverse population without restrictions. In spatial design, VR has been applied in various contexts, often focusing on behavioral intentions and psychological perceptions. Small living spaces are gaining more popularity as an affordable housing solution and an environmentally sustainable lifestyle. Despite their growing demand, user experiences of small living spaces have not been empirically tested. Specifically, the impact of users’ different characteristics on the psychological responses to small living spaces has rarely been studied. In this study, we used three-dimensional (3D) virtual mock-ups to test how subjects of different genders and personality types perceived different shapes of a small space. A 2 × 2 factorial design was used to test two different wall length-width combinations (short vs. long floor plan shape) with two different ceiling heights (low vs. high). Forty-eight participants were randomly assigned to watch one of the four small living spaces. After watching the virtual walkthrough video, participants filled out the questionnaires on their perceptions. The results show that floor plan shape had a significant impact on place attachment. Participants reported greater place attachment to the space with a shorter floor plan than the longer one. In addition, higher ceiling height is closely related to functional and goal-oriented connections. The impact of the floor plan shape of the space on place attachment differed according to gender, age, and personality. Participants with higher extrovert scores reported greater functional connections to higher ceiling height. Men reported significantly more affective ties with longer floor plans than shorter ones. The older age group perceived longer floor plans to be more functional than the shorter ones.